AAV2-MEDIATED GENE DELIVERY OF SFASL AS A NEUROPROTECTIVE THERAPY IN GLAUCOMA - Gregory-Ksander, Meredith; Marshak-Rothstein, Ann; Ksander, Bruce R (2025)
Methods for treating glaucoma and/or Fas ligand-dependent inflammatory conditions in a subject using soluble Fas ligand (sFasL) or a fragment thereof, which may be rAAV-mediated delivery of sFasL or a fragment thereof to a subject.